1999
DOI: 10.1021/bi990796i
|View full text |Cite
|
Sign up to set email alerts
|

Selective Release, Removal, and Reconstitution of Bacteriochlorophyll a Molecules into the B800 Sites of LH2 Complexes from Rhodopseudomonas acidophila 10050

Abstract: A method is described which allows the selective release and removal of the Bchla-B800 molecules from the LH2 complex of Rhodopseudomonas acidophila 10050. This procedure also allows reconstitution of approximately 80% of the empty binding sites with native Bchla. As shown by circular dichroism spectroscopy, the overall structures of the B850-only and reconstituted complexes are not affected by the pigment-exchange procedure. The pigments reconstituted into the B800 sites can also efficiently transfer excitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 33 publications
4
66
0
Order By: Relevance
“…Release of B800 was confirmed by the disappearance of the absorption peak at 800 nm. Reconstitution of the LH2 complex could be achieved by incubating the B850-only complexes with Bchla in a variety of detergent systems including octyl-glucoside, dodecylmaltoside (laurylmaltoside) or Triton, followed by removal of excess Bchla by ionexchange chromatography [123]. Comparison of the CD spectra of native LH2, B850-only complexes and reconstituted complexes in both visible and near IR spectral regions showed that the structures of the inner core of carotenoids and Bchla-B850 were very similar (indicating that the overlap of orbitals in the excited state of the latter had been preserved).…”
Section: The Interactions Between Chromophores In the Light Harvestinmentioning
confidence: 99%
“…Release of B800 was confirmed by the disappearance of the absorption peak at 800 nm. Reconstitution of the LH2 complex could be achieved by incubating the B850-only complexes with Bchla in a variety of detergent systems including octyl-glucoside, dodecylmaltoside (laurylmaltoside) or Triton, followed by removal of excess Bchla by ionexchange chromatography [123]. Comparison of the CD spectra of native LH2, B850-only complexes and reconstituted complexes in both visible and near IR spectral regions showed that the structures of the inner core of carotenoids and Bchla-B850 were very similar (indicating that the overlap of orbitals in the excited state of the latter had been preserved).…”
Section: The Interactions Between Chromophores In the Light Harvestinmentioning
confidence: 99%
“…To understand fully how these naturally occurring pigment–protein complexes harvest light so efficiently, it is necessary to employ spectroscopic tools that reveal directly the dynamics and efficiency of energy transfer and the nature of the excited energy states associated with the bound pigments. The spectroscopic studies are aided by the ability to make systematic alterations in the structures of the light-harvesting complexes, and then to examine how these changes manifest themselves in the spectroscopic observables, dynamics of energy transfer and efficiency of antenna function (Akahane et al 2004; Cammarata et al 1990; Chadwick et al 1987; Crielaard et al 1994; Croce et al 1999; Davidson and Cogdell 1981; Frank 1999; Fraser et al 1999; Morosinotto et al 2002; Olivera et al 1994; Olsen et al 1997; Plumley and Schmidt 1987; Remelli et al 1999; Struck and Scheer 1991; Struck et al 1992). …”
Section: Introductionmentioning
confidence: 99%
“…16,17 Possible reasons for the observed temperature-dependent changes of the B800 and B850 band properties are the denaturation of proteins, the dissociation of BChl molecules, and reversible changes in the BChl-BChl and BChl-protein interactions. 9,18 Since the denaturation of proteins and the dissociation of BChl molecules are irreversible reactions, 19 these two reactions should result in irreversible changes in the B800 and B850 band properties during such temperature cycles. By contrast, the changes in B800 and the B850 band properties with temperature are reversible during temperature cycles of 273 -313 K (Fig.…”
Section: Lh2 In Bulk Watermentioning
confidence: 99%